SOME PSYCHOLOGICAL ASPECTS OF TEACHING ENGLISH AS A FOREIGN LANGUAGE - Razzakova Shakhlo Bakhtiyor kizi (Journal of new century innovations, 2023)
Abstract. The article covers main theories about several psychological aspects of teaching English as a foreign language. In addition, ways of avoiding the fear learners face in communication and the role motivation are discussed.